Acceptability of background noise amongst children diagnosed with an auditory processing disorder. (2nd July 2016) - Sheehan, Gemma; Houghton, Janene; Searchfield, Grant D
Abstract : Objectives: Children with an Auditory Processing Disorder (APD) have difficulty hearing in background noise despite normal-hearing thresholds. The acceptable noise level (ANL) test assesses an individual's acceptance to background noise while listening to running speech. It was hypothesized that children with APD would have larger than normal ANL scores (poorer acceptance of background noise). Methods: This is a comparative study with a control group. Thirty-two children were tested for APD and placed into 1 of 3 groups according to their history of suspected APD, their test results and normative data, 'APD' ( n  = 14) 'pass-APD' ( n  = 10) and a group of children for whom no hearing problems had been reported by teachers or caregivers 'norm' ( n  = 8). Each child was assessed using the ANL test as well as a comprehensive behavioral APD test battery. Results: Children diagnosed with APD had significantly larger ANL scores than other children ( P  < 0.05). The ANL was significantly correlated with scores on a Frequency Pattern Test (FPT) and Random Gap Detection Task (RGDT). Significant interactions of group by age and group by memory were found for the ANL. Conclusion: The results demonstrate a strong relationship between low acceptance of background noise and some APD tests. We suggest that determination of sound acceptance at time of entry to school using a simple test such as the ANL would assist in early discovery of childrens' listening needs.